Nothing is more important or equal to Love - Panayides, Angelos (My University, 2026)
13 October 2021, 10th United Designs Biennial Online 2021 United Design Alliance, Online Exhbition Nothing is more important or equal to Love Invited participant The theme of the 10th United Designs was "Messages to Humanity" and was a call to designers to visualize our emotions, our experiences, our beliefs, our struggles, and our strengths. It was held virtually, with 70 designers from 15 nations. Organized by the United Designs Alliance (UDA)